2018
DOI: 10.1155/2018/6930269
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Coeliac Disease Food Attitudes and Behaviours Scale

Abstract: Objectives Previous studies on coeliac disease suggest that attitudes towards the gluten-free diet may contribute to the development of disordered eating. This study describes the development and validation of the Coeliac Disease Food Attitudes and Behaviours scale (CD-FAB) to measure these behaviours in coeliac disease. Research Methods and Procedures Focus groups were used to develop 33 potential questionnaire items. These items were reviewed by service users and then distributed online to 157 adults with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…While comparing the obtained results with those of Satherley et al [25], which also assessed FNS scores of CD individuals, it must be emphasized that they did not calculate the proportion of individuals showing low, medium, and high FNS scores, owing to the fact that the aim of their study was to develop a CD Food Attitudes and Behaviours Scale (CD-FAB), to identify disordered eating attitudes and behaviors, but not presentation of the FNS scores of participants. Despite the fact, that CD-FAB is brief, self-report questionnaire that shows good reliability and validity in measuring disordered eating attitudes and behaviors in CD patients, it covers a lot of themes exploring food attitudes, concerns, and eating behaviors (i.e., handling of food, trust, risk-taking, and food safety), whereas the FNS is focused only on one narrow aspect.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…While comparing the obtained results with those of Satherley et al [25], which also assessed FNS scores of CD individuals, it must be emphasized that they did not calculate the proportion of individuals showing low, medium, and high FNS scores, owing to the fact that the aim of their study was to develop a CD Food Attitudes and Behaviours Scale (CD-FAB), to identify disordered eating attitudes and behaviors, but not presentation of the FNS scores of participants. Despite the fact, that CD-FAB is brief, self-report questionnaire that shows good reliability and validity in measuring disordered eating attitudes and behaviors in CD patients, it covers a lot of themes exploring food attitudes, concerns, and eating behaviors (i.e., handling of food, trust, risk-taking, and food safety), whereas the FNS is focused only on one narrow aspect.…”
Section: Discussionmentioning
confidence: 51%
“…Till date, no study has analyzed the determinants of food neophobia in CD patients; however, two studies by Satherley [22,25] included the Food Neophobia Scale (FNS) to measure the prevalence and predictors of disordered eating behavior in women with CD [22], as well as to develop the Celiac Disease Food Attitudes and Behaviors Scale (CD-FAB) [25]. Therefore, the aim of the present study was to analyze food neophobia levels and its determinants in CD patients in comparison with other individuals who follow a GFD based on their own decision.…”
Section: Introductionmentioning
confidence: 99%
“…Using the EQ-5D and CLDQ simultaneously is the most promising approach to evaluate the HRQOL of patients with HCV infection in the present study. Compared to the generic scale, the disease specificity scale can more accurately express the specific clinical symptoms of patients [16]. We found that the HRQOL in patients with HCV infection was significantly impaired in all domains compared to that of HSs, signifying that chronic viral hepatitis is more commonly seen in the rural areas than the urban areas of China and that the chronic sequelae of chronic viral hepatitis, such as cirrhosis and HCC, may have greatly affected patients' health.…”
Section: Discussionmentioning
confidence: 89%
“…Encouraging family participation in care, including joining in person CD support groups, may help (48)(49)(50) . Consideration may be given to CD specific tools (51) . Parents, physicians and dietitians can all play a role in supporting positive eating behaviours and attitudes (12,18,19,46,(48)(49)(50)52) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Personality traits, parental psychosocial difficulties, including anxiety and depression, perceptions of costs and knowledge, as well as a diagnosable feeding or eating disorder, may also play a role in the relationship between eating behaviours and QOL, but were not Table 3 Considerations for prevention of eating difficulties in adolescents with coeliac disease Promote regular gastroenterologist visits and ongoing involvement of a registered dietitian nutritionist (RDN) specialised in coeliac disease (CD), beyond the initial diagnosis (48,49) Through conversations over time, practitioners should promote increased gluten-free diet (GFD) adherence/reduce inadvertent gluten exposures, correct any nutritional deficits, promote normal growth and development, and monitor for continued or new symptoms, including other digestive-related morbidities (48,49) Upon diagnosis, patients should be encouraged to join a CD support groups (48)(49)(50) particularly in-person if possible (50) Encourage family members involvement as part of the ongoing support team (48,49) RDNs should assess whether a patient's approach to GFD adherence may interfere with daily activities and quality of life CD specific tools may be useful in assessments. The newly developed the coeliac disease food attitudes and beliefs scale, validated in adults, may help in assessing CD-Specific food-related behaviours, although its utility with adolescents and for clinical practice is unknown (51) A nonpunitive approach to dietary counselling should be adopted (24,25) If the treatment team has concerns about a patient's eating approach that is not resolving, the patient should be referred to an eating disorder specialist (psychiatrist, psychologist, social worker) for further evaluation Psychiatric co-morbidities such as anxiety or depression should be identified, and appropriate referral undertaken measured in this study (21,52) . Despite these limitations, to our knowledge, this is the first mixed methods analysis that describes the approach towards maintaining a GFD, highlighting the need for additional eating behaviour research among adolescents with CD.…”
Section: Limitationsmentioning
confidence: 99%